Neuroprotective Effect of Vinpocetine against Lead Acetate-Instigated Neurotoxicity in Rats by Evaluation Tumor Necrosis Factor-Alpha, Interleukin-1Beta and Interleukin-10 - Ibrahim, Manal Abdulkhaliq; Abbas, Wameed Hashim; Ghalib, Muhsin Sagheer; Al-Shawi, Nada N. Najia (Iraqi Journal of Pharmaceutical Sciences, 2022)
Lead toxicity elicits neurological damage which is a well-known disorder that has been considered to be a major cause for multiple condition such as behavioral defect; mental retardation; and nerve insufficient activity.This research is designed to estimate potential protective effect of vinpocetine on neurotoxicity stimulated by lead acetate in rats.Eighteen adult rats of both sexes were randomly enrolled into three groups. Each group includes 6 rats as followings: Group I- Rats were given 0.3ml normal saline solution orally; then intraperitoneal injection of 100μl of the normal saline was given 1h later; this group was considered as control. Group II- Rats were given an intraperitoneal injection of 20mg/kg lead acetate for 5 days. Group III- Rats were orally given 3mg/kg vinpocetine, which was given 1hr before [(the IP injection of Pb every 24 hours at a dose of 20mg/kg) for 5 days and continued for 10 days]. On 11th day of the study, the brain of each animal has been surgically cut-out to make homogenate preparation to estimate tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), and interleukin-10 (IL-10) levels.Lead significantly elevated TNF-α and IL-1beta; while, it significantly decreased IL-10 levels. Vinpocetine significantly minimized IL-1beta and TNF-α; furthermore, vinpocetine significantly raise IL-10 levels at (P<0.05).Vinpocetine may have a neuro-protective activity against lead-stimulated toxicity brain of rats.